Development Assessment Of Solar Concentrating Power System for Green Energy Generation - R. A., Bakar (2010)

(untitled)
General solar power technology using photovoltaic cell to convert the sun energy directly into electric power but the efficiency is constraint by the material cost and the environmental factors. Lately, the development of the solar power move a step forward into concentrating technology where the density of the solar energy per area is multiplied from several time to few thousand time before it is convert into electric power. The breakthrough comes in many methodology based on different niche area and the concentrating solar thermal power give the most significant efficiency per unit energy cost. A detail development evaluation on solar concentrating technology has been carried out by the local university researchers to identify the future research path with lower energy cost and higher harvesting efficiency. Compared to fossil fuel based electric supply, the development of the renewable solar technology might not able to solve the current energy crisis. With the integration of hybrid system, improvement in lower production cost and compatible energy cost, the solar technology would give an alternative solution in the near future.